MAKING TEXTILE DYES FROM EXTRACT WATER PLANTS (Impatiens Balsamina L) WITH ADDITION GAMBIR AS STABILIZER - Supraptiah, Endang (Politeknik Negeri Sriwijaya, 2017)
The use of dyes from natural materials have long been used, but with the discovery of synthetic dyes are relatively easily produced and have better stability, natural dyes began to be abandoned. But it turns out the use of synthetic dyes have a negative impact on the environment and human health. One of the natural resources that have the potential for henna plant dye is water. Henna plant parts water can be used as natural dyes are the leaves that allegedly contain anthocyanins. To concentrate the dye obtained use of additives of gambier. This study aimed to study the effect of the solvent, the stability of the natural dyes to the effects of environmental conditions, and absorption of natural dyes produced in the coloring of textile materials. The solvents used are ethanol + water, ethanol and acetone. The results showed that the natural dye textiles manufacture of henna leaves water (Impatiens balsamina Linn) at the highest dye produced by ethanol. Value% yield produced by ethanol is 37.3788%.